The Aviation Industry Development and The Economic Growth in Indonesia - Utama, Bayu Dananjaya; Rezki, Jahen Fachrul (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2021)
Competition in the air transportation service business is currently experiencing very rapid development. This study looks at the effect of economic growth, population density, and provincial land transportation in Indonesia on the number of passengers and the number of cargo. This study uses statistical data on air transportation released by the Central Statistics Agency (BPS). The regression method used is the Fixed Effect. This study indicates that GDP per capita and government policies regarding upper and lower limit fares showed a significant positive effect on the number of passengers when not using the time trend. Furthermore, trucks are indicated to significantly affect cargo when they do not use the time trend. The policy to impose tariff limits can upset the market balance. When applying the upper limit rate is below the equilibrium price, it can cause excess demand.